Comparative analysis of power ramp rate control strategies for photovoltaic systems - Yan, Hein Wai (2023)
Intermittent changes in irradiance caused by passing clouds inevitably lead to fluctuations in photovoltaic (PV) power generation. To ensure the stability of a power grid with integrated solar PV generation, a battery energy storage system (BESS) is an intrinsic solution to effectively process the PV power before transmitting it into the grid. Alternatively, a PV software-based ramp rate (RR) control can be applied to mitigate the PV power fluctuations without any BESS, which is known to be cost-effective. The contribution of this paper is to compare various BESS-based and cost-effective software-based RR control strategies operating with real-time measured information, and analyze their effectiveness in regulating the PV power fluctuations. Furthermore, this paper studies the BESS utilization behavior among hardware-based control strategies, and also provides insights into which strategy is more appropriate for specific applications. The investigations are carried out through simulation case studies with a real-field one-day fluctuated irradiance profile.